The effects of centralizing Irish local government in London, as illustrated by the operation of tlie centralized audit of Irish municipal corporation accounts - Hancock, W. Neilson (Dublin Statistical Society, 1859)
The result of all this machinery and divided responsibility is, as we have seen, that the work is not done. Just as the Indian mutiny showed the folly of the double government of India, the Belfast case shows the folly of the double government of Ireland. If this was put an end to, by the Irish Office being erected into an independent department, the Lord Lieutenant would be enabled to have the corporation accounts which are sent to him each year audited under his direction in Dublin Castle, in immediate connection with the Irish Law Officers, who could advise on points of doubt and take proceedings promptly and efficiently if required, instead of waiting till the evil had grown to such height as it did by ten years of neglect in Belfast.
Read November 26th, 1858
Keywords: Local government; Centralisation; 314.15